2020
DOI: 10.1111/puar.13141
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior in the Public Sector: A Systematic Literature Review and Future Research Agenda

Abstract: This article presents a systematic literature review of organizational citizenship behavior (OCB) in the public sector. The findings show that although OCB is gaining more attention in the public sector, research often does not take specific public sector characteristics or concepts into account. Based on the available evidence, the authors develop a framework of antecedents, outcomes, mediators, and moderators of OCB. Three areas for future research are recommended: (1) regarding theory: link OCB to public se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 95 publications
(125 reference statements)
5
107
0
10
Order By: Relevance
“…Based on the previous explanation, this study aims to examine the role of POS, servant leadership, and OCB in predicting knowledge sharing, particularly in public sector organizations. In addition, the results could complement the lack of previous research concerning the consequences of OCB in the public sector (de Geus et al 2020).…”
Section: Introductionsupporting
confidence: 64%
“…Based on the previous explanation, this study aims to examine the role of POS, servant leadership, and OCB in predicting knowledge sharing, particularly in public sector organizations. In addition, the results could complement the lack of previous research concerning the consequences of OCB in the public sector (de Geus et al 2020).…”
Section: Introductionsupporting
confidence: 64%
“…Findings also indicate that respondents may yield more teaching quality and innovation (Yaakobi &Weisberg, 2020), knowledge sharing, job satisfaction, mental health, physical health, job retention, and learner-centered behaviors (De Geus, et al, 2020;Hazzi, 2018). The respondents' level of OCBs further implies that the organization (school) where they work at may have organizational efficiency and effectiveness (De Geus, et al, 2020;Hazzi, 2018;Organ, 2018) and higher productivity and better quality of service (Somech & Oplatka, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…OCB is found to be helpful in promoting quality and innovation in organization (Yaakobi &Weisberg, 2020). It facilitates knowledge sharing and promotes job satisfaction, mental health, physical health, job retention, and service-oriented behaviors among employees (De Geus, Ingrams, Tummers, & Pandey, 2020). Display of OCBs also fosters organizational efficiency as it can reduce the need for supervision, training and crisis management costs, allow managers to focus on important job functions, and encourage employees to get involved in giving constructive suggestions that may help improve the organization (Hazzi, 2018).…”
Section: Literature Review Organizational Citizenship Behaviormentioning
confidence: 99%
“…Police officers are expected to have the correct work value and be highly committed to the organization in order to improve the job achievements of the police. In addition, Kao [44] found that if supervisors could arouse the thought of police officers, inspire their aspirations and provide prospection of the police organization, their commitment to the organization could be increased and they could show more organizational citizenship behavior (OCB) [45]. Furthermore, increasing the professional commitment of police officers could also increase OCB [43].…”
Section: Association Between Education Training Effectiveness and Emmentioning
confidence: 99%